Association of circadian dysregulation with retinal degeneration and Alzheimer’s disease: a special focus on Muller glial cells - Das, Glori; Milner, Thomas E. (Frontiers in Photonics, 2024)
This review examines circadian dysregulation and the role of Müller glial cells (MGCs) in retinal degeneration associated with Alzheimer's disease (AD). Evidence supporting the interdependence of circadian rhythm (CR) disruption and AD progression is presented. Also reviweed are reports substantiating the role of MGCs in maintaining CR. Studies documenting MGC dysfunction in AD retinas suggest that gliosis, altered diurnal patterns in water homeostasis (and overall retinal layer optical properties), blood-retina barrier breakdown, and impaired ocular glymphatic clearance possibly caused by AD-associated protein deposits are relevant to disease progression. Similarities between AD and various retinopathies are explored with respect to MGC physiology and CR dysfunctionaltered mitochondrial dynamics. We propose that MGC circadian dysregulation is diagnostically and therapeutically relevant to AD retinopathy.CR refers to the timing of biological processes based on a 24-hour master clock. These processes are further controlled through the oscillating expression of core clock genes. Clock gene